2022
DOI: 10.1038/s41368-022-00160-w
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive profile of TCF1+ progenitor and TCF1− terminally exhausted PD-1+CD8+ T cells in head and neck squamous cell carcinoma: implications for prognosis and immunotherapy

Abstract: The heterogeneity of exhausted T cells (Tex) is a critical determinant of immune checkpoint blockade therapy efficacy. However, few studies have explored exhausted T cell subpopulations in human cancers. In the present study, we examined samples from two cohorts of 175 patients with head and neck squamous cell cancer (HNSCC) by multiplex immunohistochemistry (mIHC) to investigate two subsets of Tex, CD8+PD1+TCF1+ progenitor exhausted T cells (TCF1+Texprog) and CD8+PD1+TCF1− terminally exhausted T cells (TCF1−T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Upregulation of immune checkpoint inhibitors (e.g., PD-1/PD-L1) attenuates the cytolytic activity of CD8 + T cells in HNSCC (45). Here, we found that, although there was no significant difference in the total immune score between BASP1 high and BASP1 low tumors, BASP1 high ones exhibited reduced and exhausted cytotoxic CD8 + T cells, which have critical influence on immune checkpoint blockade therapy efficacy (46). Furthermore, the increased immune checkpoint inhibitors and reduced immune checkpoint stimulators in the BASP1 high group also indicated an exhausted environment (47).…”
Section: Discussionmentioning
confidence: 61%
“…Upregulation of immune checkpoint inhibitors (e.g., PD-1/PD-L1) attenuates the cytolytic activity of CD8 + T cells in HNSCC (45). Here, we found that, although there was no significant difference in the total immune score between BASP1 high and BASP1 low tumors, BASP1 high ones exhibited reduced and exhausted cytotoxic CD8 + T cells, which have critical influence on immune checkpoint blockade therapy efficacy (46). Furthermore, the increased immune checkpoint inhibitors and reduced immune checkpoint stimulators in the BASP1 high group also indicated an exhausted environment (47).…”
Section: Discussionmentioning
confidence: 61%
“…We and others have previously demonstrated that anti-PD-1 favors the selection of progenitor-exhausted T cells, with crucial effects over tumor growth [ 4 , 5 , 6 ]. Progenitor-exhausted T cells are defined to be Tcf1 + [ 12 ], whereas terminally exhausted T cells, which have poor anticancer function, are defined as PD-1 + Tim3 + [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that decreased β-catenin activity inhibited the expression of Wnt-associated genes, such as Sox9, Axin2, Tcf1, and Lef1. Transcription factors TCF1 and LEF1 could regulate the proliferation, apoptosis, and function of DCs, Treg cells, and CD8 + T cells [38][39][40]. Sox9 regulated by Wnt/β-catenin plays a key role in the polarization of macrophages [41].…”
Section: Discussionmentioning
confidence: 99%